Alvin Goldman on the Trust of Experts: Appraising Pathways to Rational Decision Making - Ibrahim, Adekunle A.; Ofuka, Courage; Nkanta, Inemesit J. (NIU Journal of Humanities, 2026)
This paper appraises pathways to rational decision making within the framework of Goldman's analysis of the trust of experts. In epistemology, knowledge from testimony has often been frown at as lacking the level of certainty associated with the traditional understanding of knowledge. This has led to testimonial scepticism: the idea that information receive from others is unreliable. However, the fact that practical challenges of life necessitate reliance on expert counsel creates a problem for rational decision making. In view of this, Alvin Goldman in his article titled “Experts: Which Ones You Should Trust?” exposes the dilemma a novice encounters when confronted with conflicting experts’ advice on critical issues of life. He outlines five criteria that justify a novice’s trust in a particular expert against the other(s). Against this backdrop, this paper seeks to ascertain whether one can ever be justified in believing an expert's testimony and what justifies the believe in that expert’s testimony. In order to achieve its objective, the paper clarifies what it means to trust and who an expert is. It presents and examines Goldman’s criteria for trusting experts to ascertain their credibility and sufficiency for rational decision making. Finally, it suggests an additional criterion to strengthen the novice trust in experts’ counsel. Keywords: Expert, Trust, Testimony, Novice, Testimonial Scepticism